1989
DOI: 10.1039/f29898500137
|View full text |Cite
|
Sign up to set email alerts
|

Rotational isomerism in monofluorobenzaldehydes

Abstract: Microwave spectra of 2-and 3-fluorobenzaldehydes have been investigated in the frequency region 26.5-40.0GHz. Only the 0-trans form of 2fluorobenzaldehyde was detected in the gas phase. Analysis of 3-fluorobenzaldehyde confirmed the existence of two rotational isomers: 0-cis and 0-trans. From relative intensity measurements the 0-cis form was shown to be more stable than the 0-trans form by 300 * 200 cal mol-'. The inertia defect values and the variation of the rotational constants with the torsional quantum n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
22
0

Year Published

1989
1989
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 0 publications
4
22
0
Order By: Relevance
“…This isomerism has previously been studied in o-FB by many analytical techniques including not only NMR [5] but also infrared [6] and microwave spectroscopy. [7] In each case, the O-trans form was found to be favored, and the current results are in concert with these findings. Evidence for this geometry was also found by analysis of the nuclear overhauser effect spectroscopy (NOESY) and Rotational nuclear overhauser effect spectroscopy (ROESY) spectra of aldehydes 1-3.…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…This isomerism has previously been studied in o-FB by many analytical techniques including not only NMR [5] but also infrared [6] and microwave spectroscopy. [7] In each case, the O-trans form was found to be favored, and the current results are in concert with these findings. Evidence for this geometry was also found by analysis of the nuclear overhauser effect spectroscopy (NOESY) and Rotational nuclear overhauser effect spectroscopy (ROESY) spectra of aldehydes 1-3.…”
Section: Resultssupporting
confidence: 86%
“…[8] The 1-D 13 C data then furnished the J (C,F) coupling constants that we were particularly interested in. Figure 2 collects this data in structural form along with established J (C,F) data for 1-fluoronaphthalene (7). [9] The most conspicuous difference in the comparison of aldehyde 1 with 7 is the diminished value of 2 J (C,F) for C2 in aldehyde 1.…”
Section: Resultsmentioning
confidence: 99%
“…T h e 0-trans 260 K 7 the o-cis form being present in greater abundance ( ' 1 conformer of 2 F B is to be strongly and probably The microwave spectra also establish the planarity o f the three exclusively favoured (2). detected conformers (1). These conclusions follow a long Perhaps the most marked disagreements about conformationhistory of disagreement about the conformational equilibria o f these compounds. '…”
Section: Introductionmentioning
confidence: 53%
“…The conformational behaviour of 2-fluoro-and 3-fluorobenzaldehyde is again a topic of discussion (1) in connection with the microwave spectra of these compounds in the gas phase. Only the spectrum of the 0-trans conformer is detected i l l for 2-fiuorobknzaldehyde ( 2~~1 .…”
Section: Introductionmentioning
confidence: 99%
“…It is found that the stable configuration of this molecule has a trans form with the vinyl group twisted by 13.6°with respect to the plane of aromatic ring. In a similar experiment, trans-2-fluorobenzadehyde appears to be planar owing to formation of a weak HÁ Á ÁF bonding [2]. In the case of 2-fluoronitrobenzene, the through-space interaction between the O atoms and the F atom causes the nitro group rotates by about 32°with respect to the ring [3].…”
Section: Introductionmentioning
confidence: 92%